Mahar Fantastis dalam Budaya Perkawinan: Antara Tuntutan Tradisi dan Prinsip Hukum Islam - Winario, Mohd; Kamalin, Muhammad (EL-EMIR Institute, 2025)
This study aims to examine the phenomenon of fantastic dowries in marriage practices in society, especially in relation to the demands of tradition and the principles of Islamic law. The main focus of this study is to analyze how the amount of dowry is influenced by local social and customary norms, and how it has the potential to deviate from the essence of dowry in Islam which reminds of ease and convenience in marriage. The method used in this study is a qualitative approach with data collection techniques in the form of in-depth interviews, observations, and documentation studies in several marriage cases that occurred in certain areas known for their high dowry demands. The results of the study show that fantastic dowries often arise due to social pressure, status symbols, and competition between families. Although not explicitly contrary to Islamic law, this practice often creates an economic burden for prospective grooms and families, and in some cases even causes delays or cancellations of marriages. This study recommends the need for education and a cultural approach that restores society's understanding of dowry as a form of symbolic respect, not a material burden.